FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN PEMILIHAN TEMPAT PERSALINAN PASIEN POLIKLINIK KESEHATAN IBU DAN ANAK DI KLINIK KELUARGA PISANGAN BARU, JAKARTA - Putri, Cindy Caludia Pandoyo; Jong, Martinus Thjia Tjen; Bernarto, Innocentius (FEB Universitas Sam Ratulangi Manado, 2021)
AbstractThe purpose of this study was to evaluate the factors that influence the decision on the place of delivery at the Maternal and Child Polyclinic (KIA), Clinic of the Keluarga Pisangan Baru (KPB). The data research technique uses quantitative methods which are carried out by giving questionnaires in the form of scale questions and direct interviews with respondents. In this study, the target population was all pregnant women at the KIA Polyclinic from October to November 2020. Purposive sampling is apllied in this research. The number of samples is 136 respondents. Then, the data were processed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique with the help of SmartPLS software. The results showed that patient behavior, distance, medical personnel services, service facilities, promotions and family roles do not have a positive effect on the decision to choose the place of delivery. Service costs do not have a negative effect on the decision to choose the place of delivery. The role of family, service facilities, and service costs have a positive effect on patient behavior. Meanwhile, distance, medical personnel service, and promotion did not have a positive effect on patient behavior. AbstrakTujuan penelitian ini adalah untuk mengevaluasi faktor-faktor yang memengaruhi keputusan tempat persalinan di Poliklinik Ibu dan Anak (KIA), Klinik Keluarga Pisangan Baru (KPB). Teknik penelitian data mengunakan metode kuantitatif yang dilakukan dengan pemberian kuesioner berupa pertanyaan berskala dan wawancara langsung dengan responden. Dalam penelitian ini target populasi adalah seluruh ibu hamil di Poliklinik KIA dalam kurun waktu Oktober-November 2020. Purposive sampling diterapkan dalam penelitian ini. Jumlah sampel sebanyak 136 responden. Kemudian, data diolah menggunakan tehnik Partial Least Squares Structural Equation Modeling dengan bantuan program SmartPLS. Hasil penelitian menunjukkan bahwa perilaku pasien, jarak, pelayanan tenaga medis, fasilitas pelayanan, promosi dan peran keluarga tidak berpengaruh positif terhadap keputusan pemilihan tempat persalinan. Biaya pelayanan tidak berpengaruh negatif terhadap keputusan pemilihan tempat persalinan. Peran keluarga, fasilitas pelayanan, dan biaya pelayanan berpengaruh positif terhadap perilaku pasien. Sedangkan, jarak, pelayanan tenaga medis, dan promosi tidak berpengaruh positif terhadap perilaku pasien.